THE PROBLEM OF NEUTRALIZING ANTIBODIES IN MANAGEMENT OF MULTIPLE SCLEROSIS - B.I. Bursagova; L.A. Pak; V.M. Studenikin; L.M. Kuzenkova (Union of pediatricians of Russia, 2011)
It is known that the interferon beta therapy is more effective for multiple sclerosis. The literature review focuses on the problem of neutralizing antibodies (NAbs) in interferon beta therapy of multiple sclerosis for children and adolescents. The authors provide domestic and foreign data concerning therapy of multiple sclerosis, NAbs negative effects on bioactivity and bioavailability of diseasemodifying treatment, methods of NAbs detection and their impact on multiple sclerosis clinical course, and approaches to management of NAbs high titers. Key words: multiple sclerosis, disease-modifying treatment, interferon beta, interferon beta-1a, interferon beta-1b, neutralizingantibodies, children. (Pediatric Pharmacology. - 2011; 8 (5): 61-64.)